Sustaining Employment of Older Workers in an Ageing Society - Gudrun Biffl; Joseph E. Isaac (Austrian Institute of Economic Research (WIFO), 2005)
A challenge facing countries with an ageing population is how to retain a larger proportion of older workers in the work force while at the same time maintaining productivity growth - the latter being a necessary condition for economic sustainability of globalised economies. Apart from conventional prejudice about the ability of older workers, a low employment rate of older workers is the result of a number of socio-economic and institutional factors, some bearing on incentives, others on skill requirements. Health issues also feature in excluding older workers from the workforce prematurely. Appropriate government, management and other institutional initiatives are called for to sustain productive employment in an ageing society. The paper deals with the relevant issues in the context of statistical data featuring labour market participation, employment characteristics, employer practices, education and training and health matters, all mainly focussed on older workers. These issues are analysed in a comparative study of Austria and Australia. Both countries face global competition as well as an ageing population. However, their institutional settings differ. Further, while in Austria the ethos of social partnership is well entrenched, in Australia managerial prerogatives have strengthened in the context of greatly weakened unionism. The paper identifies similarities and differences in the experiences of the two countries. These raise questions about appropriate initiatives to deal with the specific problems of an ageing workforce in the two countries.
Keywords: 330; Ältere Arbeitskräfte; Arbeitsbedingungen; Vergleich; Österreich; Australien; Alternde Bevölkerung